2018
DOI: 10.1111/cei.13136
|View full text |Cite
|
Sign up to set email alerts
|

Anti-nuclear antibodies in patients with breast cancer

Abstract: To study the prevalence of anti-nuclear antibodies (ANA) in breast cancer patients and its association with tumour characteristics. Ninety-one patients with breast mass detected by image studies and assigned to conduct diagnostic biopsy and eventual surgical treatment were studied for demographical, tumour data and presence of ANA. Serum of positive ANA patients was screened for the extractable nuclear antigen (ENA) profile. As comparison, 91 healthy individuals matched for age and from the same geographical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 25 publications
1
21
0
1
Order By: Relevance
“…While other authors have shown associations between autoantibodies and the occurrence of ICI-induced skin toxicity, hypophysitis, and pneumonitis (Ali et al 2019 ; Tahir et al 2019 ), we did not find such an association with ICI-induced hepatitis. Our data are in line with the previous findings that show high levels of autoantibodies in healthy volunteers (Okamoto et al 2004 ; Slight-Webb et al 2016 ) and cancer patients (Anderson et al 2015 ; Nisihara et al 2018 ). Furthermore, the previous reports similarly show no elevated titers of liver-specific autoantibodies in patients with ICI-induced hepatitis (Johncilla et al 2015 ; De Martin et al 2018 ; Zen and Yeh 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…While other authors have shown associations between autoantibodies and the occurrence of ICI-induced skin toxicity, hypophysitis, and pneumonitis (Ali et al 2019 ; Tahir et al 2019 ), we did not find such an association with ICI-induced hepatitis. Our data are in line with the previous findings that show high levels of autoantibodies in healthy volunteers (Okamoto et al 2004 ; Slight-Webb et al 2016 ) and cancer patients (Anderson et al 2015 ; Nisihara et al 2018 ). Furthermore, the previous reports similarly show no elevated titers of liver-specific autoantibodies in patients with ICI-induced hepatitis (Johncilla et al 2015 ; De Martin et al 2018 ; Zen and Yeh 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…ANA were found to be positive in ∼40% of patients with malignant tumors in two previous studies (22,23). Conversely, Shiel and Jason found a malignant disease in 2.9% of patients with positive ANA (24).…”
Section: Discussionmentioning
confidence: 81%
“…Он представляет собой спектр аутоантител, которые реагируют с различными ядерными и цитоплазматическими компонентами нормальных клеток человека [63]. Хотя АНФ является важным серологическим маркером некоторых аутоиммунных заболеваний, он также обнаруживается в сыворотке крови пациентов с различными злокачественными опухолями [64]. Ряд исследователей показали, что АНФ может служить предиктивным маркером ответа на иммунотерапию.…”
Section: успехи молекулярной онкологии / Advances In Molecular Oncologyunclassified